The Interrelationship between Abscisic Acid and Reactive Oxygen Species Plays a Key Role in Barley Seed Dormancy and Germination - Ishibashi, Yushi; Aoki, Nozomi; Kasa, Shinsuke; Sakamoto, Masatsugu; Kai, Kyohei; Tomokiyo, Reisa; Watabe, Gaku; Yuasa, Takashi; Iwaya-Inoue, Mari (Frontiers in Plant Science, 2017)
Seed dormancy is one of the adaptive responses in the plant life cycle and an important agronomic trait. Reactive oxygen species (ROS) release seed dormancy and promote seed germination in several cereal crops; however, the key regulatory mechanism of ROS-mediated seed dormancy and germination remains controversial. Here, we focused on the relationship between hydrogen peroxide (a ROS) and abscisic acid (ABA) in dormant and non-dormant barley seeds. The hydrogen peroxide (H2O2) level produced in barley seed embryos after imbibition was higher in non-dormant seeds than in dormant seeds. H2O2 regulated the ABA content in the embryos through ABA-8′-hydroxylase, an ABA catabolic enzyme. Moreover, compared with non-dormant seeds, in dormant seeds the activity of NADPH oxidase, which produces ROS, was lower, whereas the activity of catalase, which is a H2O2 scavenging enzyme, was higher, as was the expression of HvCAT2. Furthermore, precocious germination of isolated immature embryos was suppressed by the transient introduction of HvCAT2 driven by the maize (Zea mays) ubiquitin promoter. HvCAT2 expression was regulated through an ABA-responsive transcription factor (HvABI5) induced by ABA. These results suggest that the changing of balance between ABA and ROS is active in barley seed embryos after imbibition and regulates barley seed dormancy and germination.